PENINGKATKAN KEMAMPUAN ANALISIS, SINTESIS, DAN EVALUASI MELALUI PEMBELAJARAN PROBLEM SOLVING - Pardjono & Wardaya (LPMPP Universitas Negeri Yogyakarta, 2009)
AbstractImproving Analytical, Synthetic, and Evaluative Skills through Problem-Solving Learning. This study aims to improve high-level cognitive abilities of thestudents of SMKN 2 Wonosari through problem solving. This study was an actionresearch study conducted in two cycles. The subjects were 32 Year 2 students ofAutomotive Mechanical Engineering of SMKN 2 Wonosari. The instrument was theresearcher, equipped with teacher observation sheets and student and teacherfeedbacks. The data were analyzed by the quantitative descriptive technique,supported by the qualitative technique. The study showed that the atmosphere wasmore conducive for learning, indicated by the improvement of students activenessin asking questions, the decrease of off-tasks, and the decrease of ones dependenceon others. The level of class disturbance tended to decrease, indicated by thedecreasing number of relaxed and noisy students. There was an improvement oflearning mastery although it was relatively small. The improvement of studentscognitive abilities was high, indicated by their scores that tended to increase andtheir work reports after learning.Keywords: analytical, synthetic, and evaluative skills, problem solving